2012
DOI: 10.1177/0269881111430748
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of switching antipsychotic drug treatment to aripiprazole or ziprasidone for improving metabolic profile and atherogenic dyslipidemia: a 12-month, prospective, open-label study

Abstract: We studied the effects of switching antipsychotic drug-treated patients with schizophrenia or bipolar disorder who evidenced adverse metabolic side effects as indicated by a triglyceride/high-density lipoprotein ratio (TG/HDL) ≥ 3.5 to aripiprazole (ARIP; 5-30 mg/day, n = 24) or ziprasidone (ZIP; 40-160 mg/day, n = 28). Anthropometric and metabolic measures, psychopathology, quality of life and motor adverse effects were assessed over a 52-week period with evaluations at baseline, 6, 12, 26 and 52 weeks. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 75 publications
(88 reference statements)
1
33
0
1
Order By: Relevance
“…Certain atypical antipsychotics such as olanzapine and clozapine are strongly associated with adverse metabolic changes, including weight gain, hyperglycemia, and dyslipidemia [18][19][20][21][22] , while other atypical antipsychotics such as aripiprazole and ziprasidone have been shown to have a lower liability for metabolic disruption 23,24 .…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Certain atypical antipsychotics such as olanzapine and clozapine are strongly associated with adverse metabolic changes, including weight gain, hyperglycemia, and dyslipidemia [18][19][20][21][22] , while other atypical antipsychotics such as aripiprazole and ziprasidone have been shown to have a lower liability for metabolic disruption 23,24 .…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Studies have consistently shown that switching from other atypical antipsychotics to ziprasidone is associated with long-term weight loss and improvement of metabolic indices 23,25,26 ; however, there have been no studies of the impact of ziprasidone on the distribution and prevalence of risk factors for MetS in subjects with schizophrenia or related psychotic disorders. This represents the first prospective and long-term (1 year) study of the effect of an atypical antipsychotic on MetS risk factors among this population.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…In those studies, the participants recruited were those who failed to achieve satisfactory response, had poor tolerability for metabolic side effects, or whose conditions had been stable under previous antipsychotic treatment (Alptekin et al, 2009;Chen et al, 2012;Harvey et al, 2004;Lee et al, 2013;Rossi et al, 2008;Simpson et al, 2008;. In contrast, the participants in the present study had not used antipsychotic medications for at least 3 months and the majority of them were firstepisode subjects.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 98%
“…4 of 25 effects of treatment (Alptekin et al, 2009;Chen et al, 2012;Harvey et al, 2004;Lee et al, 2013;Rossi et al, 2008;Simpson et al, 2008;Weiden et al, 2003a,b). In contrast, there has been only one pilot trial of a combination therapy of ZIP and OLZ, and this did not find additional benefits of ZIP as an adjuvant in chronic schizophrenia (Henderson et al, 2009).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation